One swallow doesn't make a summer: A note - Mitesh Kataria (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Maniadis et al. (2013) present a theoretical framework that aims at providing insights into the mechanics of proper inference. They suggest that a decision about whether to call an experimental finding noteworthy, or deserving of great attention, should be based on the calculated post-study probability. Although I in large agree with most points in Maniadis et al. (2013), this note raises some important caveats.
Keywords: C11; C12; C80; 330; Bayes' theorem; methodology